Home range and social analyses in a mouth brooding frog: testing the coexistence of paternal care and male territoriality. (30th July 2014) - Valenzuela‐Sánchez, A.; Harding, G.; Cunningham, A. A.; Chirgwin, C.; Soto‐Azat, C.
Abstract A link between paternal care and territoriality has been described in several anuran species. The southern Darwin's frog (Rhinoderma darwinii) has developed a highly specialized form of paternal care known as neomelia, in which males ingest developing embryos and transport them in their vocal sacs until metamorphosis is completed. Based on the main components of territoriality described in amphibians: site fidelity, resource limitation and defence (e.g. of oviposition sites and egg clutches), we hypothesized that R. darwinii males exhibit territoriality. To investigate this, we used a multi‐method approach that involved estimating home range and movements, performing social network analyses and monitoring potential egg attendance. Forty‐five individual frogs and three egg clutches were monitored in a population from southern Chile between December 2010 and February 2011. Site fidelity was found across all groups (juveniles, females, non‐brooding males and brooding males) based on small movements between captures (mean ±1 se; 0.96 ± 0.11 m) and small net displacement (2.95 ± 0.55 m). Home ranges were small (1.82 ± 0.54 m; range: 0.1–16 m2) and did not differ significantly among groups. We did not find evidence of male territoriality, instead male frogs exhibited high home range overlapping and intra‐group association. No frogs of either sex were ever seen attending eggs. This evidence supports Wells' suggestion; territoriality in anuran species with parental care should be expected only if males defend oviposition sites. Conversely, females did not exhibit home range overlapping and showed evidence of very low intra‐group association. This study has thrown up a range of additional questions with regard to temporal segregation between non‐brooding males, the roles of male and female calls during reproduction, potential female territoriality and what kind of signals triggers egg ingestion by males.